Evaluating the palatability of an oral nutritional supplement (Livity®): A consumer-based, cross-sectional study - Khan, Jahanzeb Kamal; Adnan Ghafoor; Siddiqi , Mohammed Rehan Omar; Ali Nasir; Unsharah Jahanzeb (International Journal of Endorsing Health Science Research, 2022)
Background: There is a substantial global market for dietary supplements that are frequently used. These products are meant to supplement diets while also enhancing health and wellness. Fewer studies have been conducted on sensory and consumer science compared to the substantial quantity of dietary supplement research on nutrition, dietetics, and medicine. Hence the present study aimed to assess the consumer's attitude toward the physical and sensory attributes of the nutritional supplement. Methodology: 262 consenting non-diabetic subjects of either gender≥ 40 years of age participated in this cross-sectional study. After enrollment, the subjects were requested to consume 53.8 gm of nutritional supplement dissolved in 195 ml of cold water, followed by an interview-based survey. The consumer’s preference for product sensory and physical characteristics such as appearance, taste, aroma, mouth feel, and post-consumptions feel was inquired. Preferences for the oral (Vanilla flavor) nutritional supplement (Livity®). Factors were assessed using the scoring test of a 7-point numerical scale, i.e., ranging from 1 (Strongly Disagree) to 7 (Strongly Agree). Results: Around 66.50% of subjects valued the taste of the nutritional supplements the most, followed by flavor (13.0%), aroma (9.20%), color (5.60%), energizing effect (3.60%), mouth feel (3.10%) and aftertaste (0.50%). The mean score for all the physical and sensory parameters was higher than 5, except for grainy mouth feel (mostly perceived as a negative attribute) and energetic feeling post-consumption. Around 92.4% agreed that the mouth feel of the consumed, oral nutritional supplement was smooth, 75.8% agreed on flavor quality, 70.7% were satisfied with the taste, and 82.8% reported that the smell was pleasant. Conclusion: It is concluded that the physical and sensory attributes of the oral nutritional supplement (Livity®) were highly rated in this consumer attitude-based survey.